Evaluation of Diuretic Activity of Aqueous and Hydro Methanolic Crude Extracts and Solvent Fraction of the Hydromethanolic Flower Extract of Erica Arborea L. (Ericaceae) in Swiss Albino Mice - Wondimu NL; Mengistie MG; Yesuf JS (Dove Medical Press, 2024)
Nardos Lema Wondimu,1,* Mestayet Geta Mengistie,2,* Jibril Seid Yesuf2,* 1Department of Pharmacy, College of Medicine and Health Sciences, Wolkite University, Wolkite, Ethiopia; 2Department of Pharmacology, College of Medicine and Health Sciences, University of Gondar, Gondar, Ethiopia*These authors contributed equally to this workCorrespondence: Nardos Lema Wondimu, Tel +251910540868, Email nardoslema123@gmail.comPurpose: To evaluate the diuretic effects of aqueous (AQ) and hydromethanolic crude extract (HM) the as well as the solvent fractions of the HM extract from Erica arborea flowers in mice.Methods: Mice were administered AQ and HM crude extracts, along with solvent fractions of HM extracts of E. arborea flowers, including HXF (n-hexane fraction), EAF (ethyl acetate fraction), and AQF (aqueous fraction), at doses ranging from 100 to 400 mg/kg orally. The effects of these extracts and solvent fractions on urine and salt excretion over 5 hours were compared to the effects of the solvent used for reconstitution and a standard drug (furosemide 10 mg/kg), as well as to each other.Results: The HM crude extract at a lower dose (100 mg/kg) significantly increased urine volume and salt excretion starting from the 3rd h compared to the AQ crude extract. Similar effects were observed for EAF. Notably, the HM extract and its EAF at 400 mg/kg showed comparable urine and salt excretion profiles to the standard drug.Conclusion: This study demonstrated that HM extract and EAF promote better diuresis, likely due to their saluretic properties. Furthermore, it confirms the diuretic activity of Erica arborea flowers.Keywords: diuresis, natriuresis, urine electrolyte, urine pH, mice